The family life of old people : an inquiry in East London - Townsend, Peter (Penguin Books, 1963)
The publication focuses on the social aspects and possible problems of old people ́s family life in East London. Written for proffesional public.
Keywords: Social Problems; Londýn; sociologie; rodina; sociologické faktory; sociální psychologie; průzkumy a dotazníky; Psychology, Social; Aged; London; Surveys and Questionnaires; senioři; sociální problémy; Sociological Factors; Family